Tecnologia e otimismo crítico em Egbert Schuurman. - Paixão, Wendell Gonzaga da (2024)
This thesis aims to address the philosophy of technology's state of the art in general and specifically in the work of Egbert Schuurman. The goal is to situate Schuurman's position in the philosophy of technology's development and present it as a successful response to the optimism critical dilemma concerning technology. The working hypothesis is that Egbert Schuurman's philosophical proposal to adopt critical optimism is the best and most sensible solution to the problem that underlies the reflections of several philosophers who address the topic of technology in the past and the present. Philosophical research must seek relationships with other areas of human knowledge to promote a more complete understanding of life and human actions. In this dissertation, some specific human dimensions called into dialogue are technology, philosophy, and ethical implications for the contemporary world. Given this framework, the significance of the present work lies in that the philosophical aspects existing in the phenomena of technology and their implications provide a rich theoretical instrument for analyzing and understanding reality and technological functionality in our contemporary society. Therefore, the present work presents and philosophically analyzes the optimistic and pessimistic positions regarding technology in light of Egbert Schuurman's philosophy of technology, which advocates an approach here labeled as critical optimism.